2007
DOI: 10.1152/ajpendo.00381.2006
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prolactin redirects secretory vesicle traffic in rabbit lacrimal acinar cells

Abstract: -During pregnancy, lymphocytes infiltrating the rabbit lacrimal gland disperse to the interacinar space from their normal focal concentrations, basal fluid secretion decreases, pilocarpine-induced fluid secretion increases, and stimulated fluid protein concentration decreases. Ductal epithelial cell prolactin (PRL) content increases and redistributes from the apical to the basal-lateral cytoplasm. A replication-incompetent adenovirus vector for rabbit PRL (AdPRL) was used to test the hypothesis that increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…21 The decrease of lacrimal gland fluid protein concentration can be attributed to the prolactin-induced redirection of merocrine secretion from the exocrine direction to the paracrine direction. 22,52 However, the decrease of basal fluid production rates in a setting of increased rose Bengal staining and an evidently competent fluid production mechanism suggests that the sensorimotor loop that acutely regulates fluid production is altered in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The decrease of lacrimal gland fluid protein concentration can be attributed to the prolactin-induced redirection of merocrine secretion from the exocrine direction to the paracrine direction. 22,52 However, the decrease of basal fluid production rates in a setting of increased rose Bengal staining and an evidently competent fluid production mechanism suggests that the sensorimotor loop that acutely regulates fluid production is altered in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Exposure to mediators that are not cytokines but, rather, G protein-coupled receptor agonists, can also interfere with cholinergically induced Ca 2þ elevation and exocrine b-hexosaminidase secretion. These include the muscarinic cholinergic agonist, carbachol (CCh), at a submaximal dose, 23 and the biogenic amines, histamine, and serotonin (5-HT).…”
mentioning
confidence: 99%
“…A GFP signal was detected by Western blotting, and its band intensity was measured using the Odyssey imaging software. According to previously established methods (49), secretion into culture medium was normalized to total pellet protein in each well. In previous studies, we showed that only 20 -30% of total cellular syncollin-GFP is released during a typical stimulation period with CCH (14,25).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, rabbit lacrimal acini seem to follow a similar distribution for these exocytotic proteins as those described in rat pancreatic acini [28] . In fact, like pancreatic acini [11][12][13][14] , apical exocytosis in rabbit lacrimal acini could also be redirected to the basolateral membrane surface by prolactin [29] . The distinct localization of these exocytotic proteins within the family of exocrine tissues is of fundamental importance.…”
Section: Discussionmentioning
confidence: 99%